SELF EFFICACY, SELF ACTUALIZATION, JOB SATISFACTION, ORGANIZATION CITIZENSHIP BEHAVIOR (OCB), EFFECT ON EMPLOYEE PERFORMANCE - Umar Burhan (Universitas Muhammadiyah Ponorogo, 2019)
Human resources are an important asset in achieving organizational goals. One of the factors that influence the success rate of an organization is employee performance. The purpose of this study is to determine the effect of self efficacy, self-actualization, job satisfaction and organization citizenship behavior (OCB) on employee performance in PT. Ispat Panca Putera (IPP), either simultaneously or partially. data collection was done by questionnaire and analyzed by using multiple linear regression analysis, F test and t test. The sample used in this study is 60 respondents from the total employee population of 150 people, using simple random sampling method.